免疫缺陷患儿合并结核分枝杆菌感染的临床特征分析 (Zhongguo Dang Dai Er Ke Za Zhi, 2020)
OBJECTIVE: To study the clinical features of Mycobacterium tuberculosis infection in children with secondary immunodeficiency disease (SID) versus primary immunodeficiency disease (PID). METHODS: A retrospective analysis was performed on the medical data of children with immunodeficiency and Mycobacterium tuberculosis infection (36 children with SID and 52 with PID) and 108 children with Mycobacterium tuberculosis infection but without immunodeficiency (control group). RESULTS: The onset age in the PID group was significantly lower than those in the control and SID groups (P < 0.05), and the proportation of males in the PID group was significantly higher than those in the control and SID groups (P < 0.05). Compared with the control group, the SID and PID groups had significantly lower incidence rates of tuberculosis poisoning symptoms (night sweeting, weight loss, fatigue and loss of appetite) and positive rate of PPD test (P < 0.05), as well as a significantly higher incidence rate of the involvement of ≥ 3 pulmonary lobes (P < 0.05). The children with PID tended to have the involvement of multiple organs (P < 0.05). The SID group had a significantly higher incidence rate of miliary shadow on chest CT than the control and PID groups (P < 0.05). The PID group had a significantly lower positive rate of IFN-gamma release assay (IGRA) than the control and SID groups (P < 0.05). Mycobacterium tuberculosis infection manifested as latent tuberculosis infection (36.1%) and active tuberculosis (63.9%) in the SID group. The infection mainly manifested as bacille Calmette-Guérin disease in the PID group (90.4%), among whom 2 children (3.8%) also had tuberculosis. CONCLUSIONS: Children with immunodeficiency and Mycobacterium tuberculosis infection have atypical clinical symptoms, with a high incidence rate of disseminated infection and low positive rates of PPD and IGRA tests, which may lead to misdiagnosis and missed diagnosis. Children with immunodeficiency should undergo regular tuberculosis screening for early identification and intervention.